Harm as reported by affected others: A population-based cross-sectional Finnish Gambling 2019 study - Lind Kalle; Castrén Sari; Hagfors Heli; Salonen Anne H. (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study investigates the prevalence of being an affected other (AO) of a person with problem gambling; and the associations between being an AO and socio-demographics, gambling behaviour, health-related correlates and the amount and type of gambling-related harm (GRH) for the AOs. Furthermore, perspectives of the affected family members (AFMs) and close friends (ACFs) were acknowledged. Cross-sectional, random sample Finnish Gambling population-based survey data (n = 3,994) were collected in 2019. AOs were identified using a question with seven options. Information on GRH was sought using structured questions. One-fifth (21.2 %) of all respondents were AOs, men being typically ACFs and women being more often AFMs. Being an AO was associated with younger age, gambling participation, having a gambling problem of their own and health barriers such as psychological distress. AFMs experienced GRH more often and the amount of different GRHs was greater among the AFMs. The most common harm category experienced by the AOs was emotional harm. Both health-related issues and the amount of GRHs was largest among the AFMs. A substantial amount of GRH was also experienced by ACFs. The study suggests that support could be tailored for AFMs and ACFs, based on their AO status and individual needs. A public health approach for effective harm prevention in primary, secondary and tertiary levels are discussed.